HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SISWA SMP NEGERI 1 RAMBAH KELAS IX PADA MASA PANDEMI COVID 19 - Sila Feroza; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the positive and significant relationship between learning motivation and learning outcomes of Physical Education and Health of Students of SMP Negeri 1 Rambah Class IX during the Covid-19 Pandemic. The method used is descriptive method with correlation test analysis technique. The population used was 64 students of class IX.1 and IX.2. The sampling technique used was total sampling consisting of 32 people in class IX.1 and 32 people in IX.2, thus the number of samples in this study was 64 people. The results of this study on the product moment correlation test, showed that N = 64 at a significant level of 5% was obtained at 0.246 and rcount (pearson correlations) was obtained at 0.733. If rtable 0.246 > rcount 0.733, then there is a relationship or correlation between learning motivation and learning outcomes for Physical Education and Health for Students of SMP Negeri 1 Rambah Class IX during the Covid-19 Pandemic.Key Words: Learning motivation, Learning outcomes